Islamic Values and Local Wisdom - Oktaviani, Diah (Proceedings of Annual Conference for Muslim Scholars, 2024)
This article discusses the importance of collaboration between Islamic values and local wisdom in fostering cultural harmony within multicultural societies. In the context of Indonesia, which is rich in diversity, the synergy between Islamic teachings emphasizing tolerance, mutual respect, and justice and local wisdom that reflects regional traditions and cultures becomes essential in building a harmonious society. The research employs a qualitative approach, utilizing interviews and field studies in several communities that successfully integrate these values. The findings indicate that this collaboration not only enhances social awareness and solidarity among groups but also reduces the potential for conflicts arising from differences. Consequently, the article recommends the importance of education and the strengthening of these values within local curricula as a strategic step toward maintaining social harmony in the modern era. In conclusion, the collaboration between Islamic values and local wisdom plays a central role in constructing an inclusive and peaceful cultural identity.